Sustainability-oriented application of value stream mapping: a review and classification - Lee, Jocelyn Ke Yin; Gholami, Hamed; Mat Saman, Muhamad Zameri; Ngadiman, Nor Hasrul Akhmal; Zakuan, Norhayati; Mahmood, Salwa; Omain, Siti Zaleha (IEEE, 2021)
Notwithstanding the research on rening lean tools for the sake of sustainable development is slowly progressing, sustainability-oriented application of value stream mapping has received undivided attention from practitioners and researchers. Going through the literature highlights that there is a lack of research in integrating and systematising the available knowledge on this lean tool, which is regarded as a visual process-based method to make sustainable progress over the time-based and green concepts of wastes to also assess and improve the societal sustainability performance of organisations. Hence, this paper has been aimed at presenting the ndings of a systematic literature review on value stream mapping from the triple bottom line point of view. It classies and codes the main studies in the context as well as provides a research agenda with nine recommendations that may advance this under-studied eld. To narrow the gap in the current literature, this article also proposes a sustainability indicator set that would considerably contribute to guiding and strengthening the state-of-the-art research on successful implementation of the application. Besides, the ndings indicate that more investigations are needed on employing survey and conceptual methodologies, applying comparative and cross-industry perspectives, developing sustainability indicator sets particularly societal metrics, and considering the stakeholders' benets from adopting sustainability-oriented value stream mapping. The research on the convergence of this sustainability-oriented application and new paradigms such as IR 4.0 and/or Circular Economy should be also strengthened.